Analysis of regularities in the publication of environmental issues: the case of the State of Chihuahua, Mexico - Cervantes Rendón, Esmeralda; Garza Almanza, Victoriano; Contreras Garcia, Edgar (Revista General de Información y Documentación, 2013)
The State of Chihuahua, Mexico shares a border with the United States of America who shares water sources and air basins. Like any region has a particular situations in environmental issues. In this study we identified publications on environmental themes in the State of Chihuahua by analyzing in Scimago Journal Ranking (SJR), the Atlas of Mexican Science (ACM), the software Publish or Perish and the Environmental Virtual Library of Chihuahua State (BVA), which contains specialized information on environment issues of the state of Chihuahua and is classified in the themes of Water, Air, Land, Biodiversity, Energy, Waste, Environmental Health and Other. Was found in the country of Mexico and the State of Chihuahua the most interest is on Water studies. It was also noted the importance of using tools like BVA, providing specialized information on a region to an analysis of publications of a specific area as the state of Chihuahua.